Primer on Quality in the Analytical Laboratory, A - Kenkel, John (CRC Press, 2009)
Today's industrial laboratory analyst encounters issues such as quality control, quality assurance ISO 9000, standard operating procedures, calibration, standard reference materials, statistical control, control charts, proficiency testing, validation, system suitability, chain of custody, good laboratory practices, protocol, and audits. In a well-written and readable style, A Primer on Quality in the Analytical Laboratory provides an introduction to quality, standards, and regulations in the analytical laboratory and serves as a valuable resource to the myriad of laboratory practices.